Peran Elemen Komunikasi Visual pada Media Berita Online Terhadap Kesiapan Mental Pasca Pandemi Covid–19 di Bali - Swandi, I Wayan; Julianto, I Nyoman Larry (Universitas Komputer Indonesia, 2020)
The Covid–19 pandemic has a major impact on all sectors of life, especially with regard to the aspect of mental and emotional health of each individual. The Corona virus problem was followed by massive dissemination of information through online-based news media, regarding the development of the spread area and an increase in the number of sufferers. With the involvement of illustrations and text (headlines) as elements of visual stimulation in the delivery of information during the pandemic, it is necessary to understand interpretatively regarding their role in the mental and emotional readiness of readers in facing the post-Covid-19 pandemic in Bali. The qualitative analysis method on the visual approach is carried out in an effort to understand the psychological perceptions which is constructed in the communication structure. The results of the research indicate that the element of visual stimulus in the form of illustrations and text (headlines) is the stimulus that is capable of providing an organism process in generating responses for readers, so that information that seems contradictory will create psychological perceptions. The implicit impact is in the form of disagreement which results in the conception of 'resistance' to the message conveyed. Visual communication design elements in an infodemic indirectly contribute to the mental and emotional readiness of the target audience to be able to face the new normal era of life or post-pandemic life.